2001
DOI: 10.1159/000047450
|View full text |Cite
|
Sign up to set email alerts
|

Dental Amalgam Fillings and the Amount of Organic Mercury in Human Saliva

Abstract: We studied differences in the amounts of organic and inorganic mercury in saliva samples between amalgam and nonamalgam human study groups. The amount of organic and inorganic mercury in whole saliva was measured in 187 adult study subjects. The mercury contents were determined by cold–vapor atomic absorption spectrometry. The amount of organic and inorganic mercury in paraffin–stimulated saliva was significantly higher (p<0.001) in subjects with dental amalgam fillings (n = 88) compared to the nonamalgam stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 8 publications
1
50
0
3
Order By: Relevance
“…Leistevuo et al had taken advantage of the CVAAS technique for analyzing saliva samples like the present study. In their research, the amount of mercury in saliva was significantly higher (P < 0.001) in subjects with dental amalgam fillings, compared to the non-amalgam study groups [44].…”
Section: Discussionmentioning
confidence: 84%
“…Leistevuo et al had taken advantage of the CVAAS technique for analyzing saliva samples like the present study. In their research, the amount of mercury in saliva was significantly higher (P < 0.001) in subjects with dental amalgam fillings, compared to the non-amalgam study groups [44].…”
Section: Discussionmentioning
confidence: 84%
“…Although mercury-containing dental amalgam is truly the most important source of vapor and inorganic mercury in the general population [2], it is possible that mercury forms (species) in oral cavity are not only inorganic, as the article by Leistevuo et al cited by the authors points out [3]. Having shown that both methyl and ethyl mercury are present in saliva samples of mercury amalgam bearers, [4][5][6] it is now essential to determine whether organic mercury generated from dental amalgam may contribute to the levels of hair mercury in individuals who are exposed to mercury amalgam fillings, as seen in Fakour et al's work [1].…”
Section: Mercury In Saliva and Scalp Hair From Dental Amalgammentioning
confidence: 99%
“…A plausible biochemical explanation would involve mercury vapor (Hg 0 ) emitted from amalgams which is reduced to mercuric mercury (Hg 2 + ) and then transformed in mono-methylmercury (CH 3 Hg + ) [3] and ethyl mercury (CH 3 CH 2 Hg + ) by oral bacteria [4,6].…”
Section: Mercury In Saliva and Scalp Hair From Dental Amalgammentioning
confidence: 99%
“…Simultaneous to the blood sampling a chewing gum test was performed at the first interview [14]. All participants gave a spontaneous saliva sample of 5 ml (non activated saliva) and another 5 ml after extensive use of a chewing gum (activated saliva).…”
Section: Saliva Testing (Chewing Gum Test)mentioning
confidence: 99%